Pengaruh Citra Merek dan Kepercayaan Merek terhadap Loyalitas Merek Lipstik Wardah: - Nur Alfia; Jojok Dwiridotjahjono (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Business development in Indonesia is experiencing intense competition in various sectors, one of which is the cosmetic industry in Indonesia, namely Wardah. One of the beauty products produced by Wardah is lipstick. Wardah is one of the well-known brands and has won the trust of consumers who have received SJH from LPPOM MUI. This study aims to determine how much influence Brand Image and Brand Trust have on Brand Loyalty to Wardah Lipstick customers in Surabaya. The population in this study were 100 respondents who had purchased and used Wardah lipstick in the city of Surabaya. The research method is descriptive quantitative. The sampling technique used is purposive sampling technique with the criteria that Wardah lipstick consumers are domiciled in the city of Surabaya and are at least 17 years old. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the Brand Image (X1) and Brand Trust (X2) variables simultaneously have a significant effect on Brand Loyalty (Y), the Brand Image (X1) variable partially has a positive and significant effect on Brand Loyalty (Y), and the Trust variable Brand (X2) partially positive and significant effect on Brand Loyalty (Y). Keywords: Brand Image; Brand Trust; Brand Loyalty